An annotated catalogue of the type specimens of Phasmatodea deposited at the Zoological Museum Hamburg (ZMH) - Ragazzini, Mattia; Pamin, Jan-Henrik; Nguyen, Eileen; Hawl-Itschek, Oliver; Husemann, Martin (Zootaxa, 2024)
We here present an updated and annotated catalogue of the stick and leaf insect (Phasmatodea) types currently housed in the Zoological Museum Hamburg (ZMH), part of the Leibniz Institute for the Analysis of Biodiversity Change (LIB). We found a total of 305 type specimens, belonging to 130 species. This includes 110 primary types (45 holotypes, 13 lectotypes, 52 syntypes) and 195 paratypes and paralectotypes. Most of the species were described by Redtenbacher, others come from Zompro, Brunner von Wattenwyl, Weidner and others. We provide updated information on the taxonomy of all species. This catalogue will represent an important resource for future taxonomic work on the group.